Efeito da veloplastia intravelar sobre a nasalidade em indivíduos com insuficiência velofaríngea - Yamashita, Renata Paciello; Carvalho, Ester Luisa Leite; Fukushiro, Ana Paula; Zorzetto, Neivo Luiz [UNESP]; Trindade, Inge Elly Kiemle (ABRAMO Associação Brasileira de Motricidade Orofacial, 2012)
PURPOSE: to check the effect of secondary palatoplasty performed with intravelar veloplasty on the nasality and nasalance of patients with repaired cleft palate and velopharyngeal insufficiency (VPI) and compare the outcome among these patients, according to the degree of velopharyngeal closure as analyzed by nasopharyngoscopy. METHOD: prospective study with 40 patients of both genders, aged from 4 to 48 years, with repaired cleft palate and residual VPI, evaluated for 3 days before and 8 months after palatoplasty, on average, divided into two groups: one with 25 patients with minor defect (group I) and the other with 15 patients with medium to large defect (group II) in velopharyngeal closure. Hypernasality was evaluated perceptually and nasalance was assessed by nasometry. Differences between groups and stages were considered to be significant at the 5% level. The local Ethics Committee for Human Research approved the study. RESULTS: after surgery, we observed a reduction of hypernasality in 84% of the patients from group I, and in 73% of the patients from group II. Reduction of nasalance scores were observed in 52% of the group I cases and in 43% of the group II. CONCLUSION: secondary palatoplasty performed with intravelar veloplasty led to improvement in nasality in most of the analyzed patients. The results further demonstrated that surgery was more effective in patients with minor defects in velopharyngeal closure.

OBJETIVO: verificar o efeito da palatoplastia secundária realizada com veloplastia intravelar sobre a nasalidade e nasalância dos pacientes com fissura de palato reparada e insuficiência velofaríngea (IVF) e comparar os resultados entre estes pacientes, de acordo com o grau de fechamento velofaríngeo aferido na nasofaringoscopia. MÉTODO: estudo prospectivo com 40 pacientes de ambos os sexos, com idades entre 4 e 48 anos, com fissura de palato reparada e IVF residual, avaliado 3 dias antes e 8 meses após a palatoplastia, em média, divididos em dois grupos: um com 25 pacientes com falhas pequenas (grupo I) e outro com 15 pacientes com falhas médias a grandes (grupo II) no fechamento velofaríngeo. A hipernasalidade foi avaliada perceptivamente e nasalância foi avaliada por meio da nasometria. Diferenças entre grupos e etapas foram consideradas significativas ao nível de 5%. O estudo foi aprovado pelo Comitê de Ética para Pesquisa com Seres Humanos da Instituição. RESULTADOS: após a cirurgia, verificou-se redução da hipernasalidade em 84% dos pacientes do grupo I e em 73% dos pacientes do grupo II. Redução da nasalância foi observada em 52% dos casos do grupo I e em 43% dos pacientes do grupo II. CONCLUSÃO: a palatoplastia secundária com veloplastia intravelar levou à melhora da nasalidade na maioria dos pacientes analisados. Os resultados também demonstraram que a cirurgia foi mais efetiva nos pacientes que apresentavam falhas pequenas no fechamento velofaríngeo.
Effect of intravelar veloplasty on nasality in patients with velopharyngeal insufficiency
Keywords: Speech; Cleft Palate; Velopharyngeal Insufficiency; Fala; Fissura Palatina; Insuficiência Velofaríngea